Java plum (Syzygium cumini) extract cream effect on decreasing the number of sunburn cell on the dorsal skin of male Wistar rat (Rattus norvegicus) exposed to UV-radiation - Dinesh Tanabbal; I Gusti Ayu Dewi Ratnayanti; I Gusti Nyoman Sri Wiryawan; I Gusti Kamasan Nyoman Arijana; Ida Ayu Ika Wahyuniari (Indoscholar, 2020)
Background: The primary acute damage due to UV radiation is keratinocyte apoptosis or sunburn cell. Previous studies showed that antioxidants inhibit UV damage. Java plum (Syzygium cumini) which is found in Indonesia, was known to have a high concentration of antioxidants. This study was aimed to assess the Java plum ethanol extract cream effects on the number of sunburn cells on the dorsal skin of male Wistar rats that exposed to UV-B. Methods This experimental research was a post-test only control group design that was conducted on 30 male rats. Groups were divided into control, placebo, 5%, 10%, and 20% ethanol extract cream concentrations (P1, P2, P3, P4, and P5, respectively). The number of sunburn cell were then observed and recorded based on visual evaluation of the skin biopsy under a light microscope. Results: The mean results of P1, P2, P3, P4, and P5 were 132.67, 98.67, 118.67, 104.00, and 54.67 respectively. The control, placebo, 5%, and 10% ethanol extract cream showed no significant result (p>0.05). In contrast, 20% ethanol extract cream showed a protective effect (p<0.05). Conclusion: Java plum ethanol extract cream with 20% dose could decrease the number of sunburn cells in the skin.